Keterampilan santri Pesantren Nur Fadillah dalam pembuatan patok beton abu sekam padi - Nur Anny S. Taufieq; Muh. Idhil Maming; Raeny Tenriola (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Nur Fadhilah Pesantren is one of the educational institutions in Somba Opu district. Nur Fadhilah boarding school is educating students from primary to a secondary level which the students who are part of a poor family. In the boarding area is great but there is still a lot of unused land between the landboarding school. With extensive land boarding school, partners were asked to find a solution that could be categorized as extracurricular activities and can help the economic needs of the students. The problems encountered in this community partnership program is 1) boarding school students life skills that are still in the form of farming and fishing which is just enough to meet the daily needs of students, 2) land owned by ample boarding school and not to have been used by managers and students. in the vicinity, even though it was so potentially be utilized, 3) costs is limited to the life of students in Nur Fadhilah Pesantren 4) the students who don't get an understanding of the application of appropriate technology to make concrete stakes. Methods used in this community partnership program is a method of mentoring and methods of participatory rural approach (PRA). Method of mentoring is done to change the paradigm of society thinking in utilizing the husk of rice husk and dry the ashes as supplementary material in making reinforced concrete stakes, increase understanding in utilizing waste husk rice, the community and encourage the entrepreneurial spirit of the community. Method PRA done to excite the partner has products to be developed and partners a sense of responsibility to the product and the environment that surrounds them. The result of this partnership program is that rice husk ash which is only used for the manufacture of salt and egg cooking equipment can now be used as a raw material that has high economic value. Concrete use cement as a binder between the sandstone and broken can be replaced by reducing the amount of cement to be used as concrete stakes. The replacement of the cement material with rice husk ash could reach 25%. So the cost of production using rice husk ash pot fillers can be reduced in the amount of 22%.